2018
DOI: 10.1101/gr.230458.117
|View full text |Cite
|
Sign up to set email alerts
|

Promoter architecture determines cotranslational regulation of mRNA

Abstract: Information that regulates gene expression is encoded throughout each gene but if different regulatory regions can be understood in isolation, or if they interact, is unknown. Here we measure mRNA levels for 10,000 open reading frames (ORFs) transcribed from either an inducible or constitutive promoter. We find that the strength of cotranslational regulation on mRNA levels is determined by promoter architecture. By using a novel computational genetic screen of 6402 RNA-seq experiments, we identify the RNA heli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 75 publications
1
30
0
Order By: Relevance
“…In yeast, NMD is thought to act on long 3'UTRs [15,16], so that transcripts bearing 3'UTRs longer than 250 nucleotides are targeted by NMD (Figure 1). Recent work from our group has shown that this is mostly true and, importantly, the strength of NMD depends linearly on 3'UTR length [11] ( Figure 3B). However, native 3'UTR lengths are highly variable, ranging from 0 to 1461 nucleotides [17].…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…In yeast, NMD is thought to act on long 3'UTRs [15,16], so that transcripts bearing 3'UTRs longer than 250 nucleotides are targeted by NMD (Figure 1). Recent work from our group has shown that this is mostly true and, importantly, the strength of NMD depends linearly on 3'UTR length [11] ( Figure 3B). However, native 3'UTR lengths are highly variable, ranging from 0 to 1461 nucleotides [17].…”
mentioning
confidence: 67%
“…We found that almost all frameshifts produce a large decrease in tAI after the mutation ( Figure 3D). The change in tAI range due to frameshifts decreases mRNA levels [11] ( Figure 3A). In contrast, ~50% of errors produce 3'UTRs in the range of native 3'UTR lengths ( Figure 3D), likely unaffected by NMD [11] ( Figure 3B).…”
Section: Codon Optimality For Removing Frameshifting Errorsmentioning
confidence: 97%
See 2 more Smart Citations
“…mRNA transcription is controlled via the gene regulatory structure, comprised of coding and cis -regulatory regions that include promoters, untranslated regions (UTRs), and terminators each encoding a significant amount of information related to mRNA levels 9 . For instance, in Saccharomyces cerevisiae , properties of individual cis -regulatory regions can explain up to half of the variation in mRNA levels [10][11][12][13][14][15] . Considering that each part of the gene structure controls a specific process related to mRNA synthesis and decay 9,16,17 , as well as the overall transcription efficiency 18 , all gene parts must be concerted in perfectly timed execution in order to regulate expression.…”
Section: Introductionmentioning
confidence: 99%